(untitled) (Proceedings of Southern Federal University. Philology, 2017)
Iren U. Gats (Moscow, Russian Federation) The author presents the methodology of conducting academic classes based on the method of situational analysis. Teaching experience is presented in the form of the model of educational communication. The author describes how the activities in the cooperation in the group. The situation of total dictation is elected as an example. Students learn specific methodological situation, analyze linguistic and didactic information, identify problems of teaching the Russian language. Participant observation showed that there is a didactic relationship between the content of training of students-philologists and level of development of linguistic competence of students. A method of the case-study is considered not only as a way of teacher education, but also as a way of entering values of the professional community. Methodically competent application of technology is part of the professional training and development of the student. Key words: a method of the case-study; linguistic and methodological competence students; methods of teaching the Russian language. DOI 10.23683/1995-0640-2017-3-193-201